Pengelolaan Dana pada Perkumpulan Sosial Kongsi Kematian - Winbaktianur Winbaktianur; Liesma Maywarni Siregar; Rina Widyanti; Syarifah Farradinna (PUSAKO : Jurnal Pengabdian Psikologi, 2023)
The purpose of this activity is carrying out this community service activity at the kongsi kematian association is to obtain increased knowledge related to the management of organizational funds in social organization groups. This activity was carried out in Pampangan Nan XX Village, Lubuk Begalung sub-district, Padang City, West Sumatra Province. The result of this activity is understanding and an increased group cooperation between administrators and members of the social association of kongsi kematian.